Cinética de absorção e acúmulo de íons em plantas de sorgo submetidas ao estresse salino: regulação mediada pela fonte de nitrogênio - Coelho, Daniel Gomes (2018)
The global increase in soil salinization, mainly in irrigated areas, constitutes a threat to sustainability of food production. In previous studies, NH4+-supply as the sole nitrogen source was an effective approach to generate salt tolerance in sorghum plants. In this work, the hypotheses were that NH4+-induced salt tolerance in sorghum plants has been related to the increase of K+ uptake, generating a favorable ionic homeostasis, as well as a high maximum uptake rate and an efficient assimilation of NH4+ in organic nitrogen compounds. In order to investigate these hypotheses, sorghum plants were grown in modified Hoagland’s nutrient solution containing NO3− or NH4+ as an inorganic source of N, in the absence or presence of saline stress (75 mM NaCl). After 1 and 10 days of exposure to NaCl, six plants of each treatment were analyzed. After 1 day of salt exposure, K+ uptake and its kinetic constants (Vmax and Km) were higher in NO3−-fed plants, compared to those fed with NH4+. After 10 days of salt stress, NH4+-grown plants showed higher K+ content and lower Na+ content in shoot and roots, and thereby higher K+/Na+ ratio. NH4+ uptake, under salinity, showed higher values of Vmax and higher affinity (lower Km), compared to that of NO3−. NO3−-grown stressed plants accumulated high amounts of ammonium in the shoot, whereas in NH4+-fed plants, this was assimilated in the roots and a small part was loaded in the xylem and transported to shoot. N-total and free amino acids contents were higher in shoot of NH4+-fed plants, mainly at 10 days, in presence of NaCl. Therefore, it was found that the high Vmax value of NH4+ as well as high assimilation into organic compounds and the better distribution of ammonium in tissues is fundamental for the reduction of deleterious effects of salinity in sorghum plants. The hypothesis that NH4+ improves K+ uptake of sorghum plants under salt stress condition was refuted. However, it was possible to infer that the maintenance of the higher K+/ Na+ ratio in NH4+-grown plants, when compared to NO3−, is due to the reduction of K+ efflux. The results reinforce the evidences that NH4+ nutrition as a promising alternative to attenuate the harmful effects of salt stress in sorghum plants.